Cancerogenic effect of topical calcineurin inhibitors – a real threat or invalid concerns? - Sokołowska-Wojdyło, Małgorzata; Góralczyk, Alicja; Barańska-Rybak, Wioletta; Szczerkowska-Dobosz, Aneta (Dermatology Review/Przegląd Dermatologiczny, 2012)
The topical calcineurin inhibitors (TCIs) are broadly used in the treatment of the immunologically mediated skin diseases. Tacrolimus and pimecrolimus are approved for the therapy of atopic dermatitis (AD) in adults and children. Both drugs are effective and well-tolerated alternatives to topical glucocorticosteroids. Proactive therapy with TCIs has been shown to prevent atopic dermatitis exacerbations and to reduce their severity. New reports on the association between the use of TCIs and the occurrence of malignancy lead to concerns about their safety. The potential cancerogenic effect of the topical immunomodulators is based on their mechanism of action, data from animal studies and single case reports of neoplasia in patients applying TCIs. This article provides an overview of the available literature data concerning the increased risk of malignancy in patients with AD under treatment with tacrolimus or pimecrolimus. Current knowledge is insufficient to confirm the causal link between the therapy with TCIs and development of neoplasia. Pharmacokinetic studies have demonstrated minimal systemic absorption of TCIs and evidence of systemic immunosuppression has not been found. Moreover, risk factors of increased occurrence of malignancy in patients with AD may involve severity of disease and other treatment regimens. Even though the benefit-risk ratio of TCIs is thought to be favourable, long-term clinical studies are essential to assess the safety of prolonged application of tacrolimus and pimecrolimus.